Business travelers: vaccination considerations for this population. (April 2013) - Chen, Lin H; Leder, Karin; Wilson, Mary E
Illness in business travelers is associated with reduced productivity on the part of the employee as well as the employer. Immunizations offer a reliable method of preventing infectious diseases for international business travelers. The authors review the travel patterns of business travelers, available data on illnesses they encounter, their potential travel-associated risks for vaccine-preventable diseases and recommendations on immunizations for this population. Routine vaccines (e.g., measles, tetanus and influenza) should be reviewed to assure that they provide current coverage. The combined hepatitis A and hepatitis B vaccine with a rapid schedule offers options for those with time constraints. Other vaccine recommendations for business travelers need to focus on their destinations and activities and underlying health, taking into account the concept of cumulative risk for those with frequent travel, multiple trips or long stays.